The Role of the Family in the Moral Education of Children - Abroto, Abroto; Nugraheni, Aninditya Sri; Awliyah, Rizka Febriyani (Jurnal Basicedu, 2022)
Guidance of attention instruction is needed by a child because it greatly affects the behavior of a person's manners. A very important parental obligation is the cultivation of moral values. The research methods used in this research are the method of literature study (literature) and the approach used is qualitative approach. The purpose of this study is how important a family is in moral value education for children from childhood. How influential a family is on the growth of a child's moral values is enormous, because the family is the first environment that shapes the character of a child. Some fundamental aspects become the necessity of the family or parents when cultivating a moral attitude in the child, namely first, the value of honesty. Both are courtesy to the older man. The third is always taught with a sense of iklas in doing something. And most importantly upbringing in planting aqidah so as not to falter with the changing times